2010
DOI: 10.3390/ijerph7010303
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Depleted Uranium

Abstract: Depleted uranium (DU) is an emerging environmental pollutant that is introduced into the environment primarily by military activity. While depleted uranium is less radioactive than natural uranium, it still retains all the chemical toxicity associated with the original element. In large doses the kidney is the target organ for the acute chemical toxicity of this metal, producing potentially lethal tubular necrosis. In contrast, chronic low dose exposure to depleted uranium may not produce a clear and defined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 52 publications
2
75
1
6
Order By: Relevance
“…Depleted uranium and natural uranium are environmental pollutants that emerge from uranium-rich regions [87][88][89][90]. They are regarded as radiological hazards [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depleted uranium and natural uranium are environmental pollutants that emerge from uranium-rich regions [87][88][89][90]. They are regarded as radiological hazards [87].…”
Section: Discussionmentioning
confidence: 99%
“…A paper has mentioned many studies related to reproductive toxicity in humans and animals from uranium or depleted uranium exposure [93]. There are risks associated with long-term exposure from dusty particles of depleted uranium, and its drinking water contamination can lead to damaged lungs, kidneys, and brain [63,79,88,89,[94][95][96][97][98][99]. This study reported that 92% of radiation-exposed dwellers were not taking ionizing radiation-free drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…Leftover shells or fragments after combat can result in accidental ingestion by many bird species, who consume small particles inadvertently, or as grit to aid in their digestion (Fisher et al 2006). Depleted uranium shells or casings are also used by some factions and can cause localized soil and sediment contamination (Haavisto et al 2001;Papastefanou 2002;Briner 2010). Uranium toxicity is of concern to exposed terrestrial and freshwater plants, freshwater invertebrates and vertebrates, and mammals (Sheppard et al 2005).…”
Section: Active Combat Contaminationmentioning
confidence: 99%
“…Uranium toxicity is of concern to exposed terrestrial and freshwater plants, freshwater invertebrates and vertebrates, and mammals (Sheppard et al 2005). In mammals, uranium toxicity can be highly detrimental to development, brain chemistry, behaviour, and kidney function (Briner 2010).…”
Section: Active Combat Contaminationmentioning
confidence: 99%
“…Utarmet uran kan gi helseskader av to grunner: det er et giftig tungmetall og det avgir kortrekkende radioaktiv alfapartikkel stråling (28). Utarmet uran har en ekstremt lang halveringstid på 4,5 milliarder år.…”
Section: Antall åRlige Prøvesprengninger Av Atomvåpen I Perioden 1945unclassified